2022
DOI: 10.4103/jos.jos_5_22
|View full text |Cite
|
Sign up to set email alerts
|

The influence of obstructive sleep apnea on self-perceived dental aesthetics and need for orthodontic treatment among the general population in Makkah, Saudi Arabia

Abstract: OBJECTIVE: To assess the influence of obstructive sleep apnea on self-perceived dental appearance and need for orthodontic treatment. MATERIALS AND METHODS: A self-administered questionnaire was used in a random sample of a general adult population in Makkah region, Saudi Arabia. A total of 1014 participants completed the questionnaires, which included the STOP-BANG questionnaire, Oral Aesthetics Subjective Impact Score questionnaire, and Aesthetic Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Facial aesthetics is essential in orthodontic treatment because research has shown that a person's perception of his or her facial appearance can affect self-confidence and quality of life. [1][2][3][4][5] The aesthetic value of a person's face is determined, partly by the symmetry between the midline of the maxillary teeth and the face when smiling. The midline of the teeth in the maxilla that does not match the midline of the face is one of the asymmetry problems that patients are most aware of, with a prevalence of 20.70 %.…”
Section: Introductionmentioning
confidence: 99%
“…Facial aesthetics is essential in orthodontic treatment because research has shown that a person's perception of his or her facial appearance can affect self-confidence and quality of life. [1][2][3][4][5] The aesthetic value of a person's face is determined, partly by the symmetry between the midline of the maxillary teeth and the face when smiling. The midline of the teeth in the maxilla that does not match the midline of the face is one of the asymmetry problems that patients are most aware of, with a prevalence of 20.70 %.…”
Section: Introductionmentioning
confidence: 99%